Symptoms of Anxiety and Cardiac Hospitalizations at 12 Months in Patients with Heart Failure - Damen, Nikki L. (Springer-Verlag, 2011)
OBJECTIVE: Heart failure (HF) is a leading cause of hospitalization. Clinical and socio-demographic factors have been associated with cardiac admissions, but little is known about the role of anxiety. We examined whether symptoms of anxiety were associated with cardiac hospitalizations at 12 months in HF patients. METHODS: HF outpatients (N = 237) completed the Hospital Anxiety and Depression Scale (HADS) at baseline (i.e., inclusion into the study). A cutoff ≥8 was used to indicate probable clinical levels of anxiety and depression. At 12 months, a medical chart abstraction was performed to obtain information on cardiac hospitalizations. RESULTS: The prevalence of symptoms of anxiety was 24.9% (59/237), and 27.0% (64/237) of patients were admitted for cardiac reasons at least once during the 12-month follow-up period. Symptoms of anxiety were neither significantly associated with cardiac hospitalizations in univariable logistic analysis [OR = 1.13, 95% CI (0.59–2.17), p = 0.72] nor in multivariable analysis [OR = 0.94, 95% CI (0.38–2.31), p = 0.89]. New York Heart Association (NYHA) functional class III [OR = 3.00, 95% CI (1.08–8.12), p = 0.04] and a history of HF-related hospitalizations [OR = 1.18, 95% CI (1.01–1.38), p = 0.03] were independently associated with 12-month cardiac admissions. CONCLUSIONS: The current study found no significant association between symptoms of anxiety and cardiac hospitalizations at 12 months in HF patients. In contrast, clinical indicators (i.e., NYHA class III and a history of HF-related hospitalizations) were significantly associated with admissions due to a cardiac cause. Future studies are warranted to investigate the importance of symptoms of anxiety in HF using a larger sample size and a longer follow-up duration.